2010
DOI: 10.1177/1461445609346922
|View full text |Cite
|
Sign up to set email alerts
|

Agreement, acknowledgment, and alignment: The discourse-pragmatic functions of hao and dui in Taiwan Mandarin conversation

Abstract: This study draws on Relevance Theory (Sperber and Wilson, 1986/1995), Conversation Analysis (Sacks et al., 1974), and Politeness Theory (Brown and Levinson, 1987) in investigating a full range of discourse functions for hao and dui with reference to recurrent patterns, distributions, and forms of organization in a large corpus of talk. Special emphasis is placed on a comparison of hao and dui in combination with a small subset of discourse particles: in particular hao/hao le/ hao la/hao a/hao ba and dui/dui a/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…The second move is often referred to as an 'assessment' in CA. Assessments and assessment sequences have been extensively examined, both in and out of decisionmaking contexts (Davidson, 1984;Goodwin, 1986;Goodwin, 1987, 1992;McKinlay and McVittie, 2006;Maynard, 1984;Pomerantz, 1978Pomerantz, , 1984Sacks, 1987;Sacks et al, 1974;Schegloff, 1987;Wang et al, 2010;Wasson, 2000). When multiple participants in an interaction voice their assessments of some topic, they construct either agreement with each other or disagreement.…”
Section: Findings From Camentioning
confidence: 99%
“…The second move is often referred to as an 'assessment' in CA. Assessments and assessment sequences have been extensively examined, both in and out of decisionmaking contexts (Davidson, 1984;Goodwin, 1986;Goodwin, 1987, 1992;McKinlay and McVittie, 2006;Maynard, 1984;Pomerantz, 1978Pomerantz, , 1984Sacks, 1987;Sacks et al, 1974;Schegloff, 1987;Wang et al, 2010;Wasson, 2000). When multiple participants in an interaction voice their assessments of some topic, they construct either agreement with each other or disagreement.…”
Section: Findings From Camentioning
confidence: 99%
“…In this example, “ haode ” (ok) reflects the therapist’s positive feedback in relation to the child’s answer. In addition, this indicates that the child can either continue the conversation or start a new sequence ( Wang et al, 2010 ).…”
Section: Therapists’ Strategies Of Expressing Agreementmentioning
confidence: 99%
“…In terms of linking functions, “ hao ” is often used as a marker of closure or transition indicating discourse boundaries, while “ dui ” marks the continuity of conversation. As for the positive response functions, “ hao ” is used to express acceptance of the other speaker’s act or utterance, whereas “ dui ” conveys acknowledgment of the propositional content of the utterance produced by other speakers ( Wang et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…That is to say, they aim to design the previous turn in order to be responsive as well as to shape the next turn. WANG, Tsai, Goodman and MENG (2010) found that Okay in Taiwan Mandarin is used to show acceptance or agreement with the other speaker's move or act. In this sense, Okay occurs at the beginning of the turn.…”
Section: Introductionmentioning
confidence: 99%
“…However, when it is employed within a turn, it finishes the topic. Overall, Okay can be employed to mark boundary exchanges; to signal the relatedness of the current utterance to the previous one, and to show whether the turn is still available (WANG et al, 2010). Schegloff and Sacks (1973) also explained that Okay is used as a pre-closing statement to close the conversation.…”
Section: Introductionmentioning
confidence: 99%